A110 DGAT1 MUTATION OF LIPID TRAFFICKING ASSOCIATED WITH A RARE CASE OF CONGENITAL DIARRHEA. (26th February 2020) - Little, R; Gonska, T
Abstract: Background: Congenital diarrheas and enteropathies (CODEs) are rare and cause severe chronic diarrhea in children under 2 years of age. 1 Current genomic research has identified several monogenic defects resulting in epithelial disorders of nutrient and electrolyte transport, enzymes function, metabolism and trafficking. Aims: To discuss a rare case of congential diarrhea. Methods: Case Report. Results: A 10-month-old Ashkenazi Jewish boy was referred to Pediatric Gastroenterology for loose stools and failure to thrive. Born at 27 weeks, he was a NICU inpatient for his first 3 months of life. Explosive loose stools were first noticed after discharge and treated as cow's milk protein allergy. At aged 10 months he was admitted to his local hospital with irritability, abdominal distension, foul smelling loose stools and developmental delay. Despite an intake of 130kcal/kg/day he failed to gain weight (weight and length < 3 rd centile). His abdomen was distended but there was no organomegaly on examination. On transfer to Sick Kids he underwent extensive work up with low albumin 24 g/L but normal CBC, amylase, lipase and IgA and anti-TTG negative. The lipid profile showed hypertriglyceridemia 2.98 mmol/L (normal <0.85), low HDL 0.81 mmol/L but normal total cholesterol. Low apoliprotein A1 0.79 g/L (0.92 - 1.96), low apoliprotein B 0.54 g (0.59 - 1.46) and vitamin E deficiency 9.6 umol/L (14.5 - 33.0). Normal fecal elastase (> 500 ug/g stool). Upper GI endoscopy showed duodenal villi blunting with non-specific chronic inactive duodenitis on histopathology. Due to ongoing poor weight gain he commenced TPN. A repeat endoscopy four weeks after admission revealed patchy villous blunting, crypt hyperplasia and enterocyte vacuolization. However, ultrastructural electron microscopy examination showed normal enterocyte brush border with well-formed microvilli with no inclusions or vesicular bodies. With a differential diagnosis of chylomicron retention disorder, abetalipoproteinemia or hypolipoproteinemia he was commenced on a low-fat diet with MCT feeds. A 72-hour fecal fat collection on this diet was within normal range 5.4 mmol/day (2–7). One year later his weight is now on 3 rd centile and his albumin levels have normalized. However, triglycerides remain elevated. Whole exome sequencing identified two pathogenic variants in the DGAT1 gene; c.629_631delCCT, pSer210del and c751 + 2T>C, IVSB+2T>C. Conclusions: Diacylglycerol acyltransferase (DGAT)1 catalyzes triglyceride biosynthesis. 2 Loss of function DGAT1 gene mutations are described in several cases studies 3, 4 characterized by electrolyte transport–related diarrhea, protein-losing enteropathy and growth failure. Our cases adds to the understanding of the phenotypic and histological spectrum of DGAT1 mutations. Management strategies currently focus on growth with dietary lipid restriction, while substituting fat-soluble vitamins and essential fatty acids. Funding Agencies: CAG